Die “Gemengdheid van die Lewe”: Die Kleiner Goed of die Minste Euwel? (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2006)
Danie Strauss referred in many personal discussions to what he called “the mixture of life”. This expression refers to the mixture between the good and bad of life. Essentialy it embodies the complexity of life. In this article his expression is viewed from the compromise and Burggraeve’s view on growth ethics and ethics of the possibility. Two concepts informed the discussion: minus malum (the lesser evil) and minus bolum (the smaller good). The argument is driven that no choice should be made between these concepts but that these concepts can help to address the conflict in borderline situations. This view relates to the compromise in ethics. A compromise has to do with the choice between two conflicting norms in a borderline situation. It then necessitates a choice between one of the norms in a borderline situation. A growth ethics should assist one to grow through the current situation to the desired sitation. The value of a growth ethics is its assistance to deal with the results of the borderline situation after the choice between the lesser of two evils has been made.